Client and consultant organisations’ assessment of design-bidbuild procurement practice in Nigeria - Dada, M.O. (Penerbit UKM, 2013)
Despite criticisms, the design-bid-build (otherwise called the traditional) procurement method has been the commonest method for project delivery in both the private and public sectors of Nigeria. This study sought to investigate the assessment of client and consultant organizations on the use of the traditional method for project delivery in Nigeria. A set of 155 questionnaires were administered purposively on consulting and client organizations in Nigeria. 65 organizations responded to the questionnaire. The responses were analyzed through the use of descriptive and inferential statistical tools. Using an ordinal scale, respondents were requested to express their agreement or otherwise with twenty issues raised on traditional project procurement. The aggregation for the two groups indicates that ‘Individual participants are exploitative of loopholes in contract documents ranked first among the issues being assessed. ‘Relationships among participants breed mistrust’ ranked least among the issues. The results of the analysis further indicate that there are no significant correlations in the ranking of issues among the two groups. Some of the findings of the research do not match with some issues raised in literature about the traditional project procurement practice. It is recommended that efforts are made to engage in stakeholder management of the two groups regarding the traditional procurement process.